Response of Cucumber (Cucumis sativus L.) Varieties Against TMV (Tobacco mosaic virus) Infection - Witanto Madyo Utomo; Mimi Sutrawati; Eko Supriyono (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
The tobacco mosaic virus (TMV) is a Tobamovirus that can infect cucumber plants. There is limited information about the response of cucumber varieties against TMV infection. The research was conducted to evaluate the response of cucumber varieties to TMV infection using TMV isolates from Bogor. The evaluation of resistance to TMV isolates was conducted by sap transmission method using TMV isolates from Bogor that propagated on tobacco as the source of inoculum. Variable observations covered the period of incubation (the day after inoculation/DAI), the symptoms of the disease, disease incidence, and disease severity. The presence of viral infection was observed through the accumulation of starch and inclusions bodies. Based on the results of the research, the TMV isolate was able to infect systematically all tested plants with symptoms of which appear in the form of mosaic light to heavy with the incidence of the disease reaching 100%. Response of cucumbers varieties to TMV isolate can be categorized into resistant (Bandana F1, Neptun, and Pandu), tolerant (Ethan F1), and susceptible (Vario F1).